The nexus between Malaysia's role in the 2025 ASEAN Chairmanship, Thailand-Cambodia conflict management, and the sustainable development goals - Alim, Moh. Zahirul (Journal of National Paradigm-Based Resilience Strategy, 2026)
Background: This research aims to explain the relationship between Malaysia's role in the 2025 ASEAN chairmanship, the management of the Thailand-Cambodia conflict, and the sustainable development goals. The research focuses on examining the concrete leadership aspects carried out by Malaysia in carrying out its duties as the 2025 ASEAN Chair—especially in managing the escalation of the Thailand-Cambodia border conflict which increased sharply in 2025. Methods: This research approach is qualitative with a descriptive explanatory method, using secondary data from academic journals, books, and credible institutional reports. The analytical framework integrates Role Theory and international conflict management activities to evaluate Malaysia's leadership as Chair of ASEAN 2025. Furthermore, this study examines the relationship between conflict management and SDG Pillar 16 (Peace) through explanatory methods. Findings: The results of the study indicate a link between Malaysia's role in the 2025 ASEAN chairmanship, Thailand-Cambodia conflict management efforts, and sustainable development goals. Malaysia effectively executed four out of five international conflict management activities, including verbal intervention, diplomatic facilitation of the July 2025 ceasefire, and the deployment of a military monitoring team to prevent further casualties. Conclusions: This research concludes that despite critical notes in the management of the Thailand-Cambodia border conflict, Malaysia's role in the 2025 ASEAN chairmanship was quite significant in reducing the escalation of tensions on the Thailand-Cambodia border, thus effectively preventing new victims from military violence. Novelty/Originality of this article: The novelty of this research lies in its integrated analysis of Malaysia’s 2025 ASEAN chairmanship through the dual lenses of Role Theory and SDG 16, while simultaneously offering a critical original assessment of how regional mediation can operationalize global peace targets despite persistent institutional consensus vulnerabilities.